Efektivitas Program Kampus Mengajar dalam Kesiapan Menjadi Calon Guru pada Mahasiswa Universitas Bhinneka PGRI - Yasip Yasip; Nikita Garendieratna Fatima (Departement of Mathematics Education, 2024)
Education is changing in line with the times. One of the breakthroughs of the Ministry of Education to prepare students to become prospective teachers is through the Teaching Campus Programme. This programme provides an opportunity for students to participate in improving the quality of education in Indonesia by interacting directly with students. This study aims to describe the effectiveness of the teaching campus programme in readiness to become prospective teachers for Bhinneka PGRI University students. The research used qualitative research methods. With informants 10 representatives from Bhinneka PGRI University students who participated in the 6th batch of teaching campus programme, as well as Vice Chancellor 1 of Bhinneka PGRI University and PIC of the 6th batch of teaching campus programme. Techniques in data collection using interview techniques and documentation. data analysis techniques using 3 stages, namely the description stage, the reduction stage, and the selection stage. The results of the study indicate the effectiveness of the programme according to indicators, where prospective teacher students already have an understanding of the teaching campus programme, the accuracy of targets, time, and the achievement of the objectives of the teaching campus programme which is attended by Bhinneka PGRI University students from non-education students and education study program students who will become prospective teachers, and there are significant changes felt by students.